A Study of Cyclogenisis in the North of Western Australia - Hamilton, Gregory Stuart (Curtin University, 2002)
The region of interest in this study is the ocean area to the north of the Western Australian coast; that is, the Timor Sea. It is the tropical cyclones (TC) that generate in this area that most often affect the people and industries located in this region of Western Australia. Accordingly, it is the case that there is a continuing need to improve our understanding of these systems using both observations and numerical models. After an introduction to the problems caused by TCs in the north of Western Australia, a description is made of the study area. A review of the various meteorological systems that can be identified in the tropics is provided. This is followed by a history of research on cyclogenesis. A detailed discussion is undertaken on the current state of knowledge of tropical cyclogenesis. This theoretical understanding subsequently is applied to three case studies. Following a description of the data used and the analysis techniques, the three case studies are presented. In each case study, a system, which later becomes a tropical cyclone, is analysed during the genesis period. The three case studies examined in this thesis are, case 1 (TC Tim, 1994), case 2 (TC Elaine, 1999) and case 3 (TC Isobel, 1996). In each case, the system was studied for at least 10 days prior to it being named. This approach was adopted to ensure that any potential development was not overlooked. A system is named when it reaches sufficient intensity for gale force winds to exist in all quadrants around the centre of that system. For each case, the environment in the vicinity of the location where the system was initially identified was studied until an evolving system was identified. Monitoring of the system continued until it was named.Observations from the Geostationary Meteorological Satellite and the Defense Meteorological Satellite Program comprised the physical data set. In parallel with this data collection activity, meteorological products from a numerical model were catalogued over the same time interval. The thesis presents comparisons of the satellite products and the model output over the study period. In part, motivated by the outcomes of this comparison, it was determined to investigate further prospects for using the array of satellite-derived products that might be more appropriate for use as a forecasting support tool. Finally, as an example, a prototype index is proposed which has potential to demonstrate the degree of development of a system. In this work, for want of a name, this index is termed the Hamilton Index (HI). It uses meteorological products derived from the microwave DMSP series of satellites and provides a temporal sequence of values of the index that are applied to monitor the developing of the TC systems in the three case studies. The meteorological variables used in the index were selected because they were accepted indicators of tropical cyclogenesis identified in the research literature. When applied to the three case studies, the HI showed a significant improvement in sensitivity to the state of development of the systems, especially when compared to the computer model data examined for the case studies.